Hierarchical population structure and genetic diversity of lake trout (Salvelinus namaycush) in a dendritic system in Northern Labrador. (20th June 2013) - McCracken, Gregory R.; Perry, Robert; Keefe, Donald; Ruzzante, Daniel E.
Summary Freshwater systems are ideal for landscape genetics studies; they generally exhibit asymmetry in gene flow with populations arranged in a hierarchical, dendritic fashion. Such gene flow asymmetry has the potential to influence the distribution of genetic variation, with downstream populations typically exhibiting higher genetic diversity than headwater populations. Lake trout (Salvelinus namaycush) are widely distributed throughout temperate North America. We examined the relationship between landscape attributes, molecular genetic diversity and differentiation among lake trout populations inhabiting a hierarchically structured freshwater system in northern Labrador (the Kogaluk River drainage). Lake trout (N = 567) collected from ten lakes in this drainage were examined for polymorphism at 12 microsatellite loci. The lakes differed in connectivity, size, elevation and position within the Kogaluk catchment. We observed relatively high levels of population structure and little migration among lakes. Waterfalls were identified as a factor contributing to the observed differentiation. Although a preliminary analysis suggested an isolation‐by‐distance pattern, a subsequent decomposed pairwise regression analysis allowed the identification of outlier lakes. Removal of these outlier lakes and of one other headwater lake, isolated from the rest by several waterfalls, led to the disappearance of the isolation‐by‐distance pattern, suggesting very little or no migration among lakes despite migration being physically possible. Estimates of effective population size correlated with lake area but did not differ between headwater and downstream populations, nor was there a relationship with elevation, a result consistent with the evidence of very little to zero gene flow among lakes. Our study is the first to describe patterns of genetic diversity among lake trout populations inhabiting a spatially fragmented system in an ecologically pristine and sensitive area of northern Canada, the barren grounds of northern Labrador.